Benchmarking mobile applications for the health of people with Diabetes Mellitus - Rafael Oliveira Pitta Lopes; Sara Rodrigues Chagas; Eduardo da Silva Gomes; Joice Cesar de Aguiar Barbosa; Ítalo Rodolfo Silva; Marcos Antônio Gomes Brandão (Universidade de São Paulo, 2024)
Objective: to map the content and features of mobile applications on the management of Diabetes Mellitus and their usability on the main operating systems. Method: benchmarking research. The mapping of apps, content, and resources on the Play Store and App Store platforms was based on an adaptation of the Joanna Briggs Institute's scoping review framework. For the usability analysis, the apps were tested for two weeks and the System Usability Scale instrument was used, with scores between 50-67 points being considered borderline, between 68-84, products with acceptable usability and above 85, excellent user acceptance and, for the analysis, descriptive statistics. Results: the most prevalent contents were capillary blood glucose management, diet, oral drug therapy, and insulin therapy. As for resources, diaries and graphs were the most common. With regard to usability, two apps were considered to have excellent usability; 34, products with acceptable usability; 29, the resource may have some flaws but still has acceptable usability standards and 6, with flaws and no usability conditions. Conclusion: the content and resources of mobile applications address the fundamental points for managing Diabetes Mellitus with user-friendly resources, with usability acceptable to users and have the potential to assist in the management of Diabetes Mellitus in patients' daily lives.